Recentes aplicações sintéticas de compostos orgânicos tricloro(bromo)metila substituídos - Menezes,Fabrício Gava (2010)
This review presents the recent applications of some trihalomethyl carbinols, α,α,α-trihalogenated carbonyl compounds and trichloro(bromo)methyl-containing heterocycles, acting as high versatile synthetic precursors in organic chemistry, based on the last 10 years' literature.